Technical Note: First report on an in vivo range probing quality control procedure for scanned proton beam therapy in head and neck cancer patients. Issue 3 (6th February 2021) - Meijers, Arturs; Seller Oria, Carmen; Free, Jeffrey; Langendijk, Johannes A; Knopf, Antje C; Both, Stefan
Abstract : Purpose: The capability of proton therapy to provide highly conformal dose distributions is impaired by range uncertainties. The aim of this work is to apply range probing (RP), a form of a proton radiography‐based quality control (QC) procedure for range accuracy assessment in head and neck cancer (HNC) patients in a clinical setting. Methods and Materials: This study included seven HNC patients. RP acquisition was performed using a multi‐layer ionization chamber (MLIC). Per patient, two RP frames were acquired within the first two weeks of treatment, on days when a repeated CT scan was obtained. Per RP frame, integral depth dose (IDD) curves of 81 spots around the treatment isocenter were acquired. Range errors are determined as a discrepancy between calculated IDDs in the treatment planning system and measured residual ranges by the MLIC. Range errors are presented relative to the water equivalent path length of individual proton spots. In addition to reporting results for complete measurement frames, an analysis, excluding range error contributions due to anatomical changes, is presented. Results: Discrepancies between measured and calculated ranges are smaller when performing RP calculations on the day‐specific patient anatomy rather than the planning CT. The patient‐specific range evaluation shows an agreement between calculated and measured ranges for spots in anatomically consistent areas within 3% (1.5 standard deviation). Conclusions: The results of an RP‐based QC procedure implemented in the clinical practice for HNC patients have been demonstrated. The agreement of measured and simulated proton ranges confirms the 3% uncertainty margin for robust optimization. Anatomical variations show a predominant effect on range accuracy, motivating efforts towards the implementation of adaptive radiotherapy.